Ella Bella ballerina and The magic toyshop - Mayhew, James, 1964- (Barron's Educational Series, Inc., 2017)
In this story, Ella's ballet teacher, Miss Rosa, tells them the story of La Boutique Fantasque. The story takes place in a toyshop full of dancing dolls, she explains, as she shows them her own collection of dancing dolls and her magical music box. When Ella stays late to help clean up, she finds herself magically transported to a toyshop filled with magical dancing dolls! Ella is thrilled to meet all of the dancing dolls, but she is especially taken with two can-can dancing dolls that are in love. When two different families come to the shop and decide to each buy one of the dolls, the pair are distraught. Now Ella wonders... is there some way to keep them together forever?